Foundations of education research: Understanding theoretical components - Chu, Shiao-Wei; Hussein, Ibtesam (Journal of Interdisciplinary Studies in Education, 2015)
There are lots of challenges facingnovice researchers and graduate studentswhile committing to a research design. It iscommon to hear that graduate studentsspend countless hours learning the meaningof research components and terms. Also, itis not surprising that there are manyprofessors who struggle with finding a goodresearch book because most textbooks seemto lack practical models, examples ordiscussions to guide novice researchers tounderstand a very wide range of research ineducation. Dr. Egbert and Sanden’sFoundations of Education Research:Understanding Theoretical Componentsfills the gap with this short, practical bookcontaining literally examples and templatesto steer both beginning and establishedresearchers.